STUDI KEBIJAKAN PERLINDUNGAN KESEHATAN REPRODUKSI BAGI PEKERJA PEREMPUAN [ANALISA TERHADAP UNDANG-UNDANG KETENAGAKERJAAN NO. 13 TAHUN 2003] - Begum Fauziyah, Margaret Aliyatul Maimunah, (EGALITA, 2010)
The development of industries in the development countries nowadays has caused the availability of many chances for woman to be employee, sch as in electronical industry, textile and foodstuff manufacture. In the fact, the increasement of woman employees in the industrial company does not be followed by the guarantee of woman rights especially in getting healthy reproduction protection. This paper consist of the analysis of the right of woman employee in getting healthy reproduction protection, especially in UU No. 3/2003 about employment. In this paper, the analyst analyze the paragraphs telling about the rights of healthy reproduction in UU No. 3/2003. They are, what are the rights of healthy reproduction in woman employee told in UU No. 3/2003; how is the formulation of paragraphs in UU No.3/2003 describes the healthy reproduction in woman employee and how is the implementation of UU No. 3/2003 based on the previous studies?.The result of this analysis is UU No. 3/2003 telling about employee has arranged the rights of woman employee in getting healthy reproduction. They are, the rights of leave because of menstruation on the first and second day; the rights of leave because of give birth on 1.5 months before and after. The rights of time because of suckle and the rights of leave because ofÂ  miscarriage. However, these paragraphs not totally give protection yet. Beside, the existence of those paragraphs still have many weaknesses that perhaps let the capitalist take the benefit by using money as a power and authority to control woman employee. So that, it needs revition of UU No. 3/2003 about employment. They are recovered the right of woman employee in getting healthy reproduction and closed the capitalist to take benefit.